Effects of thickness and annealing condition on magnetic properties and thermal stabilities of Ta/Nd/NdFeB/Nd/Ta sandwiched films - 刘文峰 张敏刚 张克维 张海杰 许小红 柴跃生 (Chinese physics B, 2016)
Ta/Nd/NdFeB/Nd/Ta sandwiched films are deposited by magnetron sputtering on Si（100） substrates,and subsequently annealed in vacuum at different temperatures for different time.It is found that both the thickness of NdFeB and Nd layer and the annealing condition can affect the magnetic properties of Ta/Nd/NdFeB/Nd/Ta films.Interestingly,the thickness and annealing temperature show the relevant behaviors that can affect the magnetic properties of the film.The high coercivity of 24.1 kOe（1 Oe = 79.5775 A/m） and remanence ratio（remanent magnetization/saturation magnetization）of 0.94 can be obtained in a Ta/Nd（250 nm）/NdFeB（600 nm）/Nd（250 nm）/Ta film annealed for 3 min at 1023 K.In addition,the thermal stability of the film is also linked to the thickness of NdFeB and Nd layer and the annealing temperature as well.The excellent thermal stability can be achieved in a Ta/Nd（250 nm）/NdFeB（600 nm）/Nd（250 nm）/Ta film annealed at1023 K.